Falls risk perception measures in hospital: a COSMIN systematic review - Elissa Dabkowski; Karen Missen; Jhodie Duncan; Simon Cooper (SpringerOpen, 2023)
Abstract Falls prevention in hospital continues to be a research priority because of the poor health outcomes and financial burdens that can arise. Recently updated World Guidelines for Falls Prevention and Management strongly recommend evaluating patients' concerns about falling as part of a multifactorial assessment. The aim of this systematic review was to evaluate the quality of falls risk perception measures for adults in a hospital setting. This review was conducted using the Consensus-based Standards for the selection of health Measurement Instruments guidelines and provides a comprehensive summary of these instruments, including psychometric properties, feasibility and clinical recommendations for their use. The review followed a prospectively registered protocol, in which a total of ten databases were searched between the years 2002 and 2022. Studies were included if the instruments measured falls risk perception and/or other psychological falls constructs, if they were conducted in a hospital setting and if the target population contained hospital inpatients. A total of 18 studies met the inclusion criteria, encompassing 20 falls risk perception measures. These falls risk perception instruments were grouped into five falls-related constructs: Balance Confidence, Falls Efficacy/Concern, Fear of Falling, Self-Awareness and Behaviour/Intention. Two of the patient reported outcome measures (PROMs) received Class A recommendations (Falls Risk Perception Questionnaire and the Spinal Cord Injury-Falls Concern Scale); however, this rating is only applicable for the populations/context described in the studies. Thirteen PROMs received Class B recommendations, solidifying the need for further validation studies of these PROMs.